Frontispiece: Metastable Chiral Azobenzenes Stabilized in a Double Racemate. Issue 8 (10th February 2020) - Mohan, Amalu; Sasikumar, Devika; Bhat, Vinayak; Hariharan, Mahesh
Abstract : Cocrystals In cocrystals of octabrominated perylenediimide (OBPDI) and achiral aromatic molecules, chiral information is transferred from the OBPDI host to the achiral guests, as shown by M. Hariharan et al. in their Research Article on page 3201 .